ANALYSIS OF THE EFFECT OF WORK SCHEDULE, WORK ACTIVITIES, AND PERSONAL FACTORS ON FATIGUE WITH WORK DEMAND AS A MEDIATOR AND LIVING CONDITIONS AS A MODERATOR IN HEAVY EQUIPMENT OPERATORS AT PT. PAMAPERSADA NUSANTARA - Ari Trigar Timotius Hutahaean; Eko Fernando; Siam Arifal Effendi; Nur Damayanti; Sekar Wulan Prasetyaningtyas (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the factors influencing work fatigue among heavy equipment operators at PT. Pamapersada Nusantara (PAMA). Workplace accidents caused by operator fatigue still occur in the field; therefore, research is needed to identify the underlying causes. The variables examined in this study include work schedule, work activities, and personal factors as independent variables; work demand as a mediating variable; and living condition as a moderating variable. This research adopts a quantitative methodology utilizing a survey design, gathering data via questionnaires administered to a sample of 415 participants. The analysis of the data was conducted using a quantitative approach grounded in PLS-SEM. The findings reveal that Work Schedule and Work Activities do not exert a statistically significant direct influence on Fatigue State. However, Personal Factor demonstrates a significant positive effect on Work Demand, which subsequently has a significant impact on Fatigue State. Furthermore, mediation analysis reveals that Work Demand serves as a full mediator in the relationship between Personal Factor and Fatigue State. Meanwhile, Living Condition is not proven to act as a moderating variable nor to have a direct effect on Work Demand. These findings suggest that operator fatigue is more influenced by the perception of work demands shaped by personal factors than by structural work characteristics. Theoretically, this study extends the Job Demands–Resources (JD-R) framework by positioning Personal Factor as an antecedent that shapes the perception of Work Demand. Practically, the research results emphasize the importance of managing Work Demand perception as well as strengthening the physical capacity and psychological readiness of operators in efforts to control work fatigue.